Dyadic coping and marital adjustment during pregnancy: A cross‐sectional study of Italian couples expecting their first child. (14th January 2018) - Molgora, Sara; Acquati, Chiara; Fenaroli, Valentina; Saita, Emanuela
Abstract : Although the transition to parenthood is currently defined as a normative event, it can be potentially stressful for the couple relationship as it may contribute to psychological distress and reduced marital satisfaction. Using the systemic‐transactional conceptualisation of stress and coping as a theoretical framework, we claimed that the ability of the parents‐to‐be to adjust to their new roles and identity is influenced by dyadic coping strategies. This study examined the effects of dyadic coping on marital adjustment in a sample of 78 primiparous couples. Women and partners completed the Dyadic Adjustment Scale and the Dyadic Coping Questionnaire during late pregnancy. Data were analysed using the Actor‐Partner Interdependence Model. Results revealed that both women and partners' scores on positive dyadic coping behaviours contributed to higher marital adjustment, suggesting that risks for marital dissatisfaction may exist for couples not able to implement adaptive dyadic coping strategies, or for those unsatisfied with the implemented coping behaviours.